SOCIOLOGY OF SPACE: SEBUAH BENTANGAN TEORITIK - Hery Prasetyo (Jurnal Sejarah dan Budaya, 2013)
Abstract. This paper discusses about a discourse of "Space", which if overlooked in the landscape of social theory. Space, into a passive form for a motion history, which in it the subject, deals with social structures that repress it. In this context, the author uses the concept of Space to stress Centurm Specific dimension, which refers to how a Space concept discussed, through different theory base and how its relevance in contemporary studies. Author uses methods of discourse to form Space concept. Through this paper, the author establishes the concept of space and how the subject matter therein. The subjects in this context is no longer in the unity or solidarity among themselves, knowledge and practice. The subject is presented in the form of temporality space fragmentation.